Cellulose‐based Materials for the Removal of Heavy Metals from Wastewater – An Overview. Issue 4 (23rd June 2017) - Jamshaid, Anum; Hamid, Almas; Muhammad, Nawshad; Naseer, Ayesha; Ghauri, Moinuddin; Iqbal, Jibran; Rafiq, Sikander; Shah, Noor Samad
Abstract: Water pollution due to increase in population and high rates of wastewater generation have become serious concerns since the last few decades. Heavy metals are amongst the main wastewater pollutants due to their ability to persist in the environment. Materials and techniques are being investigated for the treatment of heavy metals in wastewater. Cellulose is one of the materials gaining attention due to its excellent physical, chemical, and mechanical properties. Cellulose‐based materials are being widely studied for the adsorption of heavy metals. This overview highlights research efforts to enhance the role of cellulose in wastewater treatment through cellulose‐based materials. It also discusses the effects of cellulose modifications such as cellulose gels, cellulose composites, cellulose derivatives, functionalized cellulose, and nanocrystalline cellulose on the capacity of heavy metals adsorption. Abstract : The naturally occurring biopolymer cellulose has the potential to be used for wastewater treatment when some modifications are introduced. The effect of cellulose modifications in the form of cellulose gels, cellulose composites, cellulose derivatives, functionalized cellulose as well as nanocrystalline cellulose for the removal of heavy metals from wastewater has been discussed.